2008
DOI: 10.1007/s00401-008-0398-7
|View full text |Cite
|
Sign up to set email alerts
|

Glial cytoplasmic inclusions in neurologically normal elderly: prodromal multiple system atrophy?

Abstract: In this study we used immunohistochemistry to screen for α-synuclein pathology in the brains of 241 individuals without clinical evidence of neurologic disease, and discovered 36 cases (15%) with incidental Lewy bodies (LBs) and one case, a 96-year-old woman (0.4%), with inclusions similar to those seen in multiple system atrophy (MSA), a nonfamilial neurodegenerative disorder characterized by parkinsonism, cerebellar ataxia and autonomic dysfunction and α-synuclein immunoreactive glial cytoplasmic inclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…In previous studies [32], [33], neurologically normal elderly subjects infrequently (0.4–0.8%) had abundant glial cytoplasmic inclusions consistent with MSA. In this context, putaminal diffusivity may be elevated in the preclinical stage of MSA-P.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies [32], [33], neurologically normal elderly subjects infrequently (0.4–0.8%) had abundant glial cytoplasmic inclusions consistent with MSA. In this context, putaminal diffusivity may be elevated in the preclinical stage of MSA-P.…”
Section: Discussionmentioning
confidence: 71%
“…MSA, which has significant potential for phenotypic overlap with PD, is defined by the presence of fibrillar α-syn, but misfolded α-syn is instead deposited in glial cytoplasmic inclusions in a brain distribution pattern that is clearly distinct from PD, based on involvement of cerebellar and cerebral white matter, pontine nuclei in the basis pontis, and inferior olivary nuclei in the medulla [38]. This distinct distribution of pathology for MSA has also been seen in autopsy cases from patients early in the disease course and in asymptomatic individuals [39][41]. Spatial resolution of PET and SPECT scans may limit the ability to distinguish some brain regions such as pons and medulla that are differentially affected in PD and MSA, but resolution should be sufficient to identify MSA-specific pathology in regions such as cerebellar and cerebral white matter.…”
Section: Discussionmentioning
confidence: 93%
“…It is observed in 5-10% of the general population over the age of 60 years and may represent a preclinical form of Lewy body disease. Anecdotal evidence has suggested that a prodromal form of MSA could also exist [79]. In cases with incidental Lewy body disease, the first a-synuclein-positive structures in the brain form in the dorsal motor nucleus of the glossopharyngeal and vagus nerves, the olfactory bulb and the anterior olfactory nucleus [19].…”
Section: Reviewmentioning
confidence: 99%